Governmental Response to Crises and Its Implications for Street-Level Implementation: Policy Ambiguity, Risk, and Discretion during the COVID-19 Pandemic. Issue 1 (2nd January 2021) - Davidovitz, Maayan; Cohen, Nissim; Gofen, Anat
Abstract: What are the implications of governmental responses to crises for street-level implementation? The COVID-19 pandemic presents a unique opportunity to compare the formal role that decision-makers require of street-level bureaucrats (SLBs) during a crisis. Textual analysis of 36 legislative documents and emergency regulations in Israel indicates that the additional duties assigned to police officers, teachers, and physicians reflect three interrelated changes in street-level implementation: increased policy ambiguity, higher risk exposure, and expanded discretion. Decision-makers' expectations of SLBs during a crisis highlight the inherent limit of policy-as-written to account for the operational, action-imperative essence of on-the-ground service delivery. Note: In the interests of space, street-level theory and the pandemic context underpinning the articles for this Special Issue are discussed in detail in the Introduction to the Issue.